Complexidade econômica e distribuição de renda dos estados brasileiros: uma análise empírica (2003 - 2021) - Silva, Leone Gomes (2025)
This dissertation investigates the relationship between economic complexity and income distribution in the period from 2003 to 2021. As an indicator of income inequality, the Gini Index provided by the PNAD of IBGE is used, which measures the degree of inequality in the distribution of individuals according to per capita household income. It is based on the hypothesis that the increase in economic complexity negatively affects income inequality in Brazilian states, with this relationship possibly being nonlinear. That is, the impacts of complexity on inequality may occur at different intensities, given the per capita GDP of the federative units (UF). To test the hypothesis, this study employed traditional panel techniques, comparing fixed and random effects models, as well as using the Threshold Model to assess the existence of linearity. The results indicate a correlation between the increase in economic complexity levels and the reduction of income inequality, suggesting that improvements in structural conditions related to diversification and productive sophistication effectively impact the income distribution process. It is observed that regions of the country with more complex states, such as the South and Southeast, have a more equitable income distribution. However, this research did not identify the existence of a nonlinear relationship between economic complexity and income inequality based on variations in per capita GDP. Furthermore, the study evaluated the impact of other variables on income inequality, such as the national real minimum wage and the share of industrial jobs, concluding that during the analyzed period, the impact of these factors on income inequality was positive. Although the result may seem counterintuitive, the analysis suggests compatibility with the structural characteristics of Brazilian states.